The Influence of Consumer Preference Groups, Customer Value, and Customer Experience on Customer Loyalty of Terajita Skincare Mejasem Store Tegal Regency - Nur Hizma, Syalwa Mutia; Hanfan, Ahmad; Wiyanti, Sari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of the skincare industry causes business competition to be higher, so companies need to preserve client loyalty as a crucial component of the long-term viability of businesses. Numerous aspects, including customer value, consumer preference groups, and customer experience. However, previous research generally only discussed some of these variables separately, so there is still limited research that combines these three variables on customer loyalty in skincare products. The study used a quantitative approach, utilising purposive sampling and Likert scale questionnaires 1–5 for data collection. The Cochran formula was utilised to calculate the sample size of 100 respondents. With The data was analysed using multiple linear regression in SPSS version 29. The results showed that the consumer preference group had a positive and significant influence on customer loyalty, with a coefficient of 0.369, customer value of 0.192, and customer experience of 0.189. Client loyalty was considerably impacted by all three factors at the same time, with a F value of 44.913 and a significance of 0.000. The outcome of the study shows that consumer preference groups, customer value, and customer experience have an important role in increasing customer loyalty at Toko Terajita Skincare Mejasem Tegal Regency.